Critical role of select peptides in the loop region of G-rich PNA in the preferred G-quadruplex topology and stability - Bose, Tanaya; Kumar, Vaijayanti A. (Tetrahedron, 2017)
An uncharged PNA 15mer sequence formed unimolecular antiparallel G-quadruplex similar to that observed for DNA-TBA. Replacement of `tt' loop regions by peptides which induce helices or turns were found to have unpresidented effect on the quadruplex topology and stability. This study opens up a completely new strategy of utilizing G-quadruplex formation to display the array of functional groups in the three dimensional space thus creating a possibility of getting closer to the dream of designed peptides with three dimensional structures as observed in catalytic protein folds. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: ESI-MS study; G-quadruplex; Peptide nucleic acid; topology